PMO within Moroccan Organizations: Towards a Synthetic Model of Implementation - El Yacoubi Zouheir; Jahidi Rachid; El Amrani Jamal (European Scientific Journal, ESJ, 2019)
The Project Management Office (PMO) is an emerging organizational structure that contributes to the improvement of both project and organizational performances, and project management maturity. Like worldwide, the PMO implementation represents a major challenge for Moroccan organizations due to several factors.. In order to explore the different aspects of PMO implementation, we adopted a qualitative approach based on conducting a set of interviews with PMO managers and experts who have implemented or have been part of a team in charge of implementing PMO. The results of the study have shown that this implementation goes through some generic steps in most cases, and the roles and functions assigned to the PMO are generally identical within the host organizations. One of the main factors influencing the PMO implementation is the top management support, seen through the organizational positioning and decision-making authority granted to the PMO. Moreover, the organizational culture and the degree of openness to innovations are determining factors too. Overall, the main challenges in PMO implementation remain change management and the maintenance of an ongoing support over time.